Distinct Mutation Pathways of Non-Subtype B HIV-1 during In Vitro Resistance Selection with Nonnucleoside Reverse Transcriptase Inhibitors - Lai, Ming-Tain (American Society for Microbiology (ASM), 2010)
Studies were conducted to investigate mutation pathways among subtypes A, B, and C of human immunodeficiency virus type 1 (HIV-1) during resistance selection with nonnucleoside reverse transcriptase inhibitors (NNRTIs) in cell culture under low-multiplicity of infection (MOI) conditions. The results showed that distinct pathways were selected by different virus subtypes under increasing selective pressure of NNRTIs. F227C and Y181C were the major mutations selected by MK-4965 in subtype A and C viruses during resistance selection. With efavirenz (EFV), F227C and V106M were the major mutations responsible for viral breakthrough in subtype A viruses, whereas a single pathway (G190A/V106M) accounted for mutation development in subtype C viruses. Y181C was the dominant mutation in the resistance selection with etravirine (ETV) in subtype A, and E138K/H221Y were the mutations detected in the breakthrough viruses from subtype C viruses with ETV. In subtype B viruses, on the other hand, known NNRTI-associated mutations (e.g., Y181C, P236L, L100I, V179D, and K103N) were selected by the NNRTIs. The susceptibility of the subtype A and B mutant viruses to NNRTIs was determined in order to gain insight into the potential mechanisms of mutation development. Collectively, these results suggest that minor differences may exist in conformation of the residues within the NNRTI binding pocket (NNRTIBP) of reverse transcriptase (RT) among the three subtypes of viruses. Thus, the interactions between NNRTIs and the residues in the NNRTIBPs of different subtypes may not be identical, leading to distinct mutation pathways during resistance selection in cell culture.